Knowledge, Skills, and Attitude of Hemodialysis Nurses in Recognizing Depression Among Hemodialysis Patients in Northern Philippines: a Mixed Methods Study. - Lea Andreau S. Liwagon; Ashley A. Bangcola (International Journal of Allied Medical Sciences and Clinical Research, 2024)
Background: Depression in hemodialysis patients is a significant concern, and hemodialysis nurses play a crucial role in its identification and management. Objective: This study aimed to explore the knowledge, skills, and attitudes of hemodialysis nurses in Iligan City towards recognizing depression in hemodialysis patients. Methods: A mixed-methods approach was employed, combining quantitative and qualitative phases. Purposive sampling selected 35 participants for the quantitative phase, and twelve of these were chosen for the qualitative phase based on extreme responses in the questionnaire. Descriptive analysis, Spearman Rank Point-Biserial Correlation, and Z-Score analysis were used in the quantitative phase, while content and thematic analyses were applied in the qualitative phase. Results: The findings reveal that the general knowledge level was average (M=0.55), and skills in identifying depression were moderate (M=3.18). Attitudes were generally neutral regarding professional confidence (M=3.22) and therapeutic optimism (M=3.25), but positive from a generalist perspective (M=3.87). In the qualitative phase, professional development, self-efficacy, and self-awareness emerged as crucial factors influencing knowledge, skills, and attitudes. Conclusion: The study provided a comprehensive understanding of the factors affecting hemodialysis nurses' knowledge, skills, and attitudes towards recognizing depression. Triangulation and validation of results highlighted the importance of professional development, self-efficacy, and self-awareness in enhancing nurses' abilities to manage depression in hemodialysis patients.